Association between self-esteem and efficacy and mental health in people with disabilities - Moon, Jong Youn; Kim, Jae-Hyun (PLOS ONE, 2021)
This study aimed to investigate the association among self-evaluations—such as self-esteem and self-efficacy—self report of depression, and perceived stress among Korean individuals with disabilities. Data from the second wave of the Panel Survey of Employment for the Disabled (collected from 2016–2018) were used. In 2016 and the follow-up in 2018, 4,033 participants were included. We estimated the annual change in both independent variables and the probability of self-report of depression and stress. Generalized estimating equation model and chi-square test were used. Compared with those whose self-esteem and self-efficacy scores were ≥30, those with scores ≤19 were, respectively, 5.825 (95% Confidence Interval [CI]: 4.235–8.011; p < .0001) and 1.494 times (95% CI: 1.233–1.810; p < .0001) more likely to have self-report of depression. The perceived stress of those with self-esteem scores ≤19 or ranging from 20–24 were, respectively, 2.036 (95% CI: 1.510–2.747; p < .0001) and 1.451 times higher (95% CI: 1.269–1.659; p < .0001) than those with self-esteem scores ≥30. There exists an inverse correlation between self-evaluations, such as self-efficacy and self-esteem, and mental health in people with disabilities. The results of this study can be used as a basis for developing interventional strategies and training and intervention programs for people with disabilities. Future research is needed to investigate potential mediating factors among Korean individuals.